New crania from Seymour Island (Antarctica) shed light on anatomy of Eocene penguins - Acosta Hospitaleche, Carolina Ileana Alicia (2013)
Antarctic skulls attributable to fossil penguins are rare. Three new penguin crania from Antarctica are here described providing an insight into their feeding function. One of the specimens studied is largely a natural endocast, slightly damaged, and lacking preserved osteological details. Two other specimens are the best preserved fossil penguin crania from Antarctica, enabling the study of characters not observed so far. All of them come from the uppermost Submeseta Allomember of the La Meseta Formation (Eocene–?Oligocene), Seymour (Marambio) Island, Antarctic Peninsula. The results of the comparative studies suggest that Paleogene penguins were long−skulled birds, with strong nuchal crests and deep temporal fossae. The configuration of the nuchal crests, the temporal fossae, and the parasphenoidal processes, appears to indicate the presence of powerful muscles. The nasal gland sulcus devoid of a supraorbital edge is typical of piscivorous species.